Digital Science - Antipova, Tatiana; Rocha, Alvaro (Advances in Intelligent Systems and Computing, 2019)
This book gathers the proceedings of the 2018 International Conference on Digital Science (DSIC'18), held in Budva, Montenegro, on October 19 - 21, 2018. DSIC'18 was an international forum for researchers and practitioners to present and discuss the latest innovations, trends, results, experiences and concerns in Digital Science. The main goal of the Conference was to efficiently disseminate original findings in the natural and social sciences, art & the humanities. The contributions address the following topics: Digital Agriculture & Food Technology Digital Art & Humanities Digital Economics Digital Education Digital Engineering Digital Environmental Sciences Digital Finance, Business & Banking Digital Health Care, Hospitals & Rehabilitation Digital Media Digital Medicine, Pharma & Public Health Digital Public Administration Digital Technology & Applied Sciences Digital Virtual Reality .